Platinum phosphinothiolato hydride complexes: synthesis, structure and evaluation as tin-free hydroformylation catalysts. Issue 9 (3rd February 2016) - Real, Julio; Prat-Gil, Esther; Pagès-Barenys, Montserrat; Polo, Alfonso; Piniella, Joan F.; Álvarez-Larena, Ángel
Abstract : Hydride1 was readily prepared and characterized: as it exchanges PPh3 very fast, it was considered a candidate catalyst for the hydroformylation of olefins. Abstract : Ligand 2-diphenylphosphinothiophenol (Hsarp) reacted with Pt(PPh3 )4 to yield trans -[PtH(sarp)(PPh3 )], which undergoes fast exchange with free PPh3 on the NMR time scale and very slowly and reversibly formed some cis -[PtH(sarp)(PPh3 )] over time in solution (11%, 24 h). Reaction of trans -[PtH(sarp)(PPh3 )] with Hsarp in boiling toluene gave cis - and trans -[Pt(sarp)2 ]; the cis isomer being more stable. These complexes were characterized by 1 H and 31 P NMR and also analyzed by XRD in the case of trans -[PtH(sarp)(PPh3 )], trans -[Pt(sarp)2 ], and cis -[Pt(sarp)2 ]. trans -[PtH(sarp)(PPh3 )] was evaluated as a preformed, tin-free hydroformylation catalyst on styrene and found active at 100 °C, at pressures over 75 bar, yielding phenylpropanal (regioselectivities up to 83% in 2-phenylpropanal), with total conversions to aldehydes up to 100% at styrene/platinum ratios from 400/1 to 1000/1 and minimal hydrogenation products.